Prabhat Dairy: The Crossover Challenge in the Indian Market. Issue 2 (September 2019) - Subramanian, Ram
Headquartered in the state of Maharashtra in India, Prabhat Dairy was one of the small, emerging private players in a growing market. India's dairy market was dominated by farmer cooperatives who controlled both milk pricing and, to a large extent, its distribution. While the commodity side of the industry featured strong incumbents and low margins, the value-added milk market was both in high growth mode and rewarded strong players with sizeable margins. Prabhat had started in 1998 serving as an intermediary to players such as Mondelez, Abbott, Perfetti Van Mele, and Britannia but now wants to move into the consumer market. It faces significant challenges in this crossover and has to come up with the right strategy to address them.